(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores three key areas of linguistics—pragmatics, Speech Act Theory, and Discourse Analysis—to provide a comprehensive understanding of language in use. Pragmatics examines how meaning is shaped by context, focusing on aspects such as deixis, implicature, and presupposition. Speech Act Theory delves into the idea that language performs actions, such as making requests or offering apologies, and identifies the illocutionary and perlocutionary acts behind utterances. Discourse Analysis takes a broader approach, studying how language operates in extended units of communication, including the organization of conversation, turn-taking, and the influence of social factors like power and ideology. Together, these three fields emphasize that language is not simply about transmitting information but is a dynamic tool for interaction, reflecting social roles, intentions, and cultural norms. The article highlights how these areas of study complement each other and enrich our understanding of communication in both everyday and formal contexts.